The Role of β-Carotene in Colonic Inflammation and Intestinal Barrier Integrity - Cheng, Junrui; Balbuena, Emilio; Miller, Baxter; Eroglu, Abdulkerim (Frontiers in Nutrition, 2021)
(1) Background: Carotenoids are naturally occurring pigments accounting for the brilliant colors of fruits and vegetables. They may display antioxidant and anti-inflammatory properties in humans besides being precursors to vitamin A. There is a gap of knowledge in examining their role within colonic epithelial cells. We proposed to address this research gap by examining the effects of a major dietary carotenoid, β-carotene, in the in vitro epithelial cell model. (2) Methods: We examined the function of β-carotene in the lipopolysaccharide (LPS)/toll-like receptor 4 (TLR4) signaling pathway. We conducted western blotting assays to evaluate expressions of TLR4 and its co-receptor, CD14. We also examined NF-κB p65 subunit protein levels in the model system. Furthermore, we studied the impact of β-carotene on the tight junction proteins, claudin-1, and occludin. We further carried out immunocytochemistry experiments to detect and visualize claudin-1expression. (3) Results: β-Carotene reduced LPS-induced intestinal inflammation in colonic epithelial cells. β-Carotene also promoted the levels of tight junction proteins, which might lead to enhanced barrier function. (4) Conclusions: β-Carotene could play a role in modulating the LPS-induced TLR4 signaling pathway and in enhancing tight junction proteins. The findings will shed light on the role of β-carotene in colonic inflammation and also potentially in metabolic disorders since higher levels of LPS might induce features of metabolic diseases.